2018
DOI: 10.1038/s41467-018-05792-3
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Single cell transcriptome profiling of retinal ganglion cells identifies cellular subtypes

Abstract: The original version of the Supplementary Information file associated with this Article contained an error in Supplementary Fig. 2. In panel c, the graph was inadvertently replaced with a duplicate of the graph in panel a. The error has now been fixed and the corrected version Supplementary Information PDF is available to download from the HTML version of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Single cell gene expression studies enable profiling of transcriptional regulation during complex biological processes and within highly heterogeneous cell populations. These studies allow the discovery of genes that identify certain subtypes of cells, or that mark an intermediate status during a biological process (Rheaume et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Single cell gene expression studies enable profiling of transcriptional regulation during complex biological processes and within highly heterogeneous cell populations. These studies allow the discovery of genes that identify certain subtypes of cells, or that mark an intermediate status during a biological process (Rheaume et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Decades of studies show that RGCs, ACs, and BCs can be divided into subtypes, each possessing characteristic anatomy, visual response, and molecular expression profile (Gollisch and Meister, 2010 ; Masland, 2012 ; Sanes and Masland, 2015 ). Many of the ~30 RGC, ~130 AC and ~13 BC types can be marked with type-specific antibodies and a full list of such markers is within sight due to an increasingly complete molecular taxonomy of the retina (Wässle et al, 2009 ; Macosko et al, 2015 ; Shekhar et al, 2016 ; Rheaume et al, 2018 ; Peng et al, 2019 ; Tran et al, 2019 ). Furthermore, many marker genes have been targeted by transgenic approaches to create an increasingly complete encyclopedia of cell-type-specific mouse lines housed at commercial repositories.…”
Section: The Retinamentioning
confidence: 99%
“…Based on morphology, functional properties, presynaptic partners and central projection patterns, approximately 30 different RGC subtypes have been characterised in the mouse retina [1,2,3]. Recent single cell RNA-seq analyses of RGCs have placed the potential number of distinct RGC subtypes at around 40 [4]. Differentiation of nascent RGCs into identifiable RGC subtypes occurs postnatally and is regulated by differential transcription factor expression.…”
Section: Specification Of Rgc Subtype Identitymentioning
confidence: 99%
“…Based on single cell RNA-seq transcriptome profiling, most subtypes of RGCs appear to be present proportionally in both eyes, although a few RGC subtypes predominate in one eye compared to the other [4]. Axonal tracing experiments also have demonstrated that ipsilaterally projecting RGCs are composed of more than one subclass of RGCs [61].…”
Section: Specification Of Rgc Subtype Identitymentioning
confidence: 99%
See 1 more Smart Citation